Building resilience: A strategic framework for managing information security risks - Abazi, Blerton (Edelweiss Applied Science and Technology, 2025)
Information security risk management and its connection to incident handling play a crucial role in today's digital landscape, where threats to data integrity and confidentiality are widespread. This study explores the importance of information security risk management and its relationship with incident handling to enhance understanding and awareness in the field. Initially, existing literature on information security risk management and incident handling was reviewed to identify research gaps. The findings revealed that comprehensive risk assessments, evaluations of an organization’s current security posture, and the deployment of advanced security technologies are key steps for building an effective information security risk management system. However, several challenges hinder successful implementation, such as organizational resistance to change, limited resources, lack of expertise, and regulatory compliance complexities. By examining how businesses handle information security incidents, this study offers valuable insights into integrating risk management with incident response. Beyond contributing to academic research, this work provides practical recommendations for organizations looking to bolster their information security in an ever-evolving environment.